The Effectiveness of Family Support on Medication Adherence in Preventing Recurrence in People with Schizophrenia: Scoping Review - Yohani Satya Putri Liman; Purnawan Junadi; Rosmala Atina Rusadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
ntroduction: Schizophrenia is a chronic mental disorder that generally occurs in individuals in their late teens to early thirties. This disorder has symptoms including irrational thoughts, delusions, persistent hallucinations, disorganised behaviour accompanied by high anxiety, and decreased cognitive function which causes schizophrenics to experience decreased social function, so they have difficulty in living their daily lives and require long-term treatment. One of the biggest challenges in managing schizophrenia is preventing recurrence. Recurrence in people with schizophrenia is often caused by their non-compliance in taking medication and following a series of treatments. The recurrence rate also depends on how the family provides support and attention to the patient, so that the patient can be obedient and regular in taking medication. Objective: This article aims to describe the effectiveness of family support on medication adherence in preventing recurrence in people with schizophrenia. Method: This research uses the literature review method by searching three databases namely Scopus, ProQuest and ScienceDirect. The selected articles were analysed using prism flowchart for data extraction. The article search results found 3 related studies. Result: The review found 68.3% of individuals with schizophrenia had low medication adherence, and more than 50% experienced a decline in social functioning. There was a relationship between medication adherence and social functioning of schizophrenia patients (r = 0.83; p = 0.001). Family support is closely related to schizophrenia adherence to medication. Schizophrenia patients who get strong family support are usually more disciplined in taking medication and have a lower risk of recurrence. Conclusion: The results of this study conclude that family support will be effective on patient compliance in taking medication, if the family has provided attention and support consistently. Thus, health care providers need to integrate family support programmes and psychoeducation on how to provide effective support as part of the treatment plan. In addition, public health policies are also needed to encourage the development of programmes that support family involvement in schizophrenia treatment.